Choice of primer pairs and PCR polymerase affect the detection of fish eDNA - Xingyue Min; Feilong Li; Xinfei Zhang; Fen Guo; Fan Zhang; Yuan Zhang (Environmental Sciences Europe, 2023)
Abstract Efficient biomonitoring is essential for fish protection and management. Environmental DNA (eDNA) has become a promising tool for fish surveys, and its accuracy and robustness are closely related to the primer pairs and DNA polymerases, especially for different environmental samples. However, there is still a lack of sufficient efforts to assess the effects of both two factors on fish biomonitoring. Here, we selected ten primer pairs in the mitochondrial 12S rRNA gene region and three commercial DNA polymerases and analyzed their effects on fish eDNA monitoring in surface water and sediment samples of Dianchi Lake. We found that primer pairs and DNA polymerases significantly affected fish biomonitoring in surface water and sediments of Dianchi Lake. First, there were significant variations in annotated fish eDNA sequences in different groups of primer pairs and DNA polymerases, the percentage of fish sequences amplified by the groups related to primers Riaz-12S and 12S-V5 was more than 90% of the total sequences. Second, the composition of different classification levels of fish taxa varied considerably across groups of primer pairs and DNA polymerases, and the groups related to primers Riaz-12S (i.e., Taq Master‒Riaz-12S, Rapid Taq‒Riaz-12S) and 12S-V5 (i.e., Taq Master‒12S-V5, Rapid Taq‒12S-V5) identified more taxa than other groups. Third, primer pairs had greater impacts on the structure of fish communities than DNA polymerases, and the interactions between two factors had more significant effects than any single one. This study highlights that primer pairs and DNA polymerases play critical roles in fish biomonitoring, and this work aimed to provide methodological guidance for assisting the design of the fish eDNA survey scheme.